Web-Based Yorùbá Numeral Translation System - Abayomi Olusola Agbeyangi; Safiriyu Eludiora; Popoola O. A (IAES International Journal of Artificial Intelligence (IJ-AI), 2016)
Yorùbá numerals have been seen as one of the most interesting but quite complicated numeral system. In this paper we present the development of a web-based English to Yorùbá numeral translation system. The system translates English numbers both in figure and text to its standard Yorùbá form. The computational processes underlying both numerals were used to formulate the model for the work. Unified Modeling language (UML) and Automata theory was used for the system design and specification. The designed system was implemented using Google Web App Engine with support for python. The result of the system evaluation using mean opinion score approach shows that the system gives a recall of 100% on all the output considered.